Pengaruh Profitabilitas Dan Kebijakan Dividen Terhadap Harga Saham Pada Perusahaan Pertambangan - Dwi Ayu Siti Hartinah H; Andi Elviani; Salmia Jumri (STIE Amkop Makassar, 2024)
The stock price is one of the things that need to be considered by investors before deciding to invest their capital in the form of shares, so that the required information is as much as possible about the stock price. This study aims to determine the effect of profitability and dividend policy on stock prices. The population of this study are mining companies listed on the Indonesia Stock Exchange in 2018-2020. The sample was selected by purposive sampling method and 11 companies were selected from 47 companies. These results show that both simultaneously and partially profitability with ROE (Return On Equity) and dividend policy with DPR (Dividend Payout Ratio) have a positive and significant effect on stock prices